2009
DOI: 10.1080/09584930802624687
|View full text |Cite
|
Sign up to set email alerts
|

A house for a daughter? Constraints and opportunities in post-tsunami Eastern Sri Lanka

Abstract: The tsunami of December 2004 caused massive human suffering and physical destruction. In its aftermath, images of helpless victims dominated public opinion and contributed to the generation of resources for the reconstruction of the affected areas. Critics soon pointed to another tsunami, this time in the form of global aid sweeping away local capacities. However valid these objections, they paid little attention to the ways in which the recipient women and men made use of the aid in both strategic and more su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Black women in the US are disproportionately represented among the poor and the disadvantaged, and after Hurricane Katrina, faced difficulty in overcoming bureaucratic obstacles associated with aid disbursement and recovery assistance, while simultaneously managing childcare employment (Tobin-Gurley, Peek, and Loomis, 2010). Men tend to enjoy the easiest access to cash through aid programmes, as in many countries, women are systematically excluded from receiving government disbursements (Enarson and Morrow, 1998;Fothergill, 1996;Thurnheer, 2009;Luna and Hilhorst, 2022). In addition, some aid programmes involve training in tradecraft, but they target men to receive training in traditionally maledominated trades like carpentry or masonry (Cupples, 2007).…”
Section: Post-disaster Access To Aid and Recovery Resourcesmentioning
confidence: 99%
“…Black women in the US are disproportionately represented among the poor and the disadvantaged, and after Hurricane Katrina, faced difficulty in overcoming bureaucratic obstacles associated with aid disbursement and recovery assistance, while simultaneously managing childcare employment (Tobin-Gurley, Peek, and Loomis, 2010). Men tend to enjoy the easiest access to cash through aid programmes, as in many countries, women are systematically excluded from receiving government disbursements (Enarson and Morrow, 1998;Fothergill, 1996;Thurnheer, 2009;Luna and Hilhorst, 2022). In addition, some aid programmes involve training in tradecraft, but they target men to receive training in traditionally maledominated trades like carpentry or masonry (Cupples, 2007).…”
Section: Post-disaster Access To Aid and Recovery Resourcesmentioning
confidence: 99%
“…Women are often categorised as individuals vulnerable to disasters (McEntire, 2012), although evidence from post-tsunami Eastern Sri Lanka indicates that pre-existing gender relationships, entitlements, networks with local NGOs, and relationships with local authorities distributing post-disaster aid have positively influenced gendered recovery (Thurnheer, 2009). Sanyal and Routray (2016) found that women, acting as part of self-help groups (SHGs), were instrumental in empowering each other, bringing other women in the community closer, aiding cash flow with bank linkages and internal lending, as well as information flow through their networks.…”
Section: Background and Contextmentioning
confidence: 99%
“…The materiality of the tsunami was certainly not lost on the people who experienced it. Fisherfolk, living in proximity to the sea, were the most heavily affected by the tsunami (Thurnheer, 2009); nearly everyone in Batticaloa I spoke with had lost a loved one. Here I turn my focus to the intimate, to what people reported of this most trying of times.…”
Section: Forcibly Enlisted? the Ocean And Sri Lanka's Armed Conflictmentioning
confidence: 99%